Associations of total arsenic in drinking water, hair and nails with serum vascular endothelial growth factor in arsenic-endemic individuals in Bangladesh. (February 2015) - Rahman, Mashiur; Mamun, Abdullah Al; Karim, Md. Rezaul; Islam, Khairul; Amin, Hasan Al; Hossain, Shakhawoat; Hossain, Md. Imam; Saud, Zahangir Alam; Noman, Abu Shadat Mohammod; Miyataka, Hideki; Himeno, Seiichiro; Hossain, Khaled
Highlights: Water, hair and nail arsenic showed unique associations with serum VEGF levels. Arsenic exposure showed precise nature of dose-response relationship with VEGF levels. All the observed associations were significant after adjusting with relevant covariates. Increased serum VEGF may cause angiogenesis for arsenic-induced cancers and CVD. Abstract: Arsenic exposure is associated with cancer and vascular diseases. Angiogenesis is an important step for the pathological development of cancer and vascular diseases. Vascular endothelial growth factor (VEGF) is a specific marker for angiogenesis. However, human study showing the association between arsenic exposure and serum VEGF levels has not yet been documented. This study was aimed to investigate the association between arsenic exposure and serum VEGF levels in the arsenic-endemic individuals in Bangladesh. A total of 260 individuals were recruited for this study. Arsenic exposure levels were measured by ICP-MS and VEGF levels were quantified using VEGF immunoassay kit. The study subjects were stratified into tertile (low, medium and high) groups based on the arsenic in water, hair and nails. Serum VEGF levels were correlated with water ( rs  = 0.363, p  < 0.001), hair ( rs  = 0.205, p  < 0.01) and nail ( rs  = 0.190, p  < 0.01) arsenic. Further, VEGF levels showed dose–response relationships with water, hair and nail arsenic. Mean VEGF levels in ⩽ 10 μg L −1, 10.1–50 μg L −1 and >50 μg L −1 groups were 91.84, 129.54, and 169.86 pg mL −1, respectively, however, significant ( p  < 0.01) difference in VEGF levels was only found in >50 μg L −1 versus ⩽10 μg L −1 groups. Significant associations of arsenic exposure with VEGF levels were found even after adjusting with relevant covariates. Therefore, these results provide evidence that arsenic exposure has a pro-angiogenic effect on humans, which may be implicated in arsenic-induced tumorigenesis and vascular diseases.